2019
DOI: 10.1038/s41467-019-12080-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing and shaping the immunogenicity of native-like HIV-1 envelope trimers with a two-component protein nanoparticle

Abstract: The development of native-like HIV-1 envelope (Env) trimer antigens has enabled the induction of neutralizing antibody (NAb) responses against neutralization-resistant HIV-1 strains in animal models. However, NAb responses are relatively weak and narrow in specificity. Displaying antigens in a multivalent fashion on nanoparticles (NPs) is an established strategy to increase their immunogenicity. Here we present the design and characterization of two-component protein NPs displaying 20 stabilized SOSIP trimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
247
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(284 citation statements)
references
References 66 publications
22
247
0
Order By: Relevance
“…Each SAXS-validated trimer (Figure 2a-d) was docked pairwise with a set of previously designed symmetric homo-oligomers 26 to generate tetrahedral, octahedral, and icosahedral arrangements using the TCdock program 16,17 . Icosahedral designs are particularly interesting as vaccine scaffolds as they have the highest valency among the cubic point group symmetries (20 trimers per particle compared to 8 for octahedra and 4 or 8 for tetrahedra), and higher valency has been shown to elicit higher antibody (Ab) titers in immunization studies 18,19,27 . To increase the probability of generating icosahedra, three naturally occurring homopentamers were also included in the docking calculations (PDB IDs 2JFB, 2OBX, and 2B98; sequences in Supplementary Table 7).…”
Section: Generation Of Two-component Nanoparticles From Designed Trimersmentioning
confidence: 99%
See 4 more Smart Citations
“…Each SAXS-validated trimer (Figure 2a-d) was docked pairwise with a set of previously designed symmetric homo-oligomers 26 to generate tetrahedral, octahedral, and icosahedral arrangements using the TCdock program 16,17 . Icosahedral designs are particularly interesting as vaccine scaffolds as they have the highest valency among the cubic point group symmetries (20 trimers per particle compared to 8 for octahedra and 4 or 8 for tetrahedra), and higher valency has been shown to elicit higher antibody (Ab) titers in immunization studies 18,19,27 . To increase the probability of generating icosahedra, three naturally occurring homopentamers were also included in the docking calculations (PDB IDs 2JFB, 2OBX, and 2B98; sequences in Supplementary Table 7).…”
Section: Generation Of Two-component Nanoparticles From Designed Trimersmentioning
confidence: 99%
“…Because previous work involving icosahedral nanoparticle scaffolds displaying HIV-1 Env trimers has shown that antigen crowding can modulate the accessibility of specific epitopes and thereby influence the humoral immune response 19,36 , we characterized the antigenicity of the BG505 SOSIP fusion nanoparticles in more detail.…”
Section: Geometriesmentioning
confidence: 99%
See 3 more Smart Citations